Teacher's Speech Act Strategies in Mediating Verbal Bullying Conflicts at YPPK Kristus Raja Dok V Bawah Elementary School - Tenri Ugi Irianto; Yunita Ruth Burdam (Pulchra Lingua: A Journal of Language Study, Literature & Linguistics, 2026)
This study specifically describes the forms of directive speech acts and the implementation of politeness strategies by the grade III C teacher at YPPK Kristus Raja Dok V Bawah Elementary School in mediating verbal bullying conflicts. Using a descriptive qualitative approach based on pragmatics, data in the form utterances were collected through the observational method and note-taking technique, and then analyzed using the pragmatic identity method. The results indicated that the teacher produced directive speech acts in the form of commands, prohibitions, and assertive-directive hybrid utterances to demand behavioral changes. These reprimands were implemented through a depersonalized Bald On-Record politeness strategy, as well as positive politeness and off-record strategies during personal mediation sessions. The selection of these linguistic strategies served to mitigate face-threatening acts toward the students. The orchestration of these pragmatic tactics created an effective perlocutionary force; it successfully dismantled the perpetrators' defensive attitudes, prompting reflection and mutual forgiveness.